2020
DOI: 10.1371/journal.pone.0239153
|View full text |Cite
|
Sign up to set email alerts
|

Reticulon-3 modulates the incorporation of replication competent hepatitis C virus molecules for release inside infectious exosomes

Abstract: Background Cell released microvesicles specifically, exosomes, play an important role in mediating immunologic escape, treatment resistance, and disease persistence of Hepatitis C virus (HCV) infection. Reports on the molecular compositions of exosomes released by cells under diverse conditions, especially during viral infections, suggest that their cargo contents are not randomly loaded. However, the precise molecular mechanisms directing the selective cargo sorting and loading inside infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Therefore, such gene could be summarized in this rule for the identification of normal controls. Similarly, RTN1 has been shown to be associated with macrophage-mediated immune suppressants, different from the immune activators in the previously discussed rules [78], thereby validating the predictions on normal control. Resources 6.8).…”
Section: Quantitative Rules Associated With Disease-specificsupporting
confidence: 64%
“…Therefore, such gene could be summarized in this rule for the identification of normal controls. Similarly, RTN1 has been shown to be associated with macrophage-mediated immune suppressants, different from the immune activators in the previously discussed rules [78], thereby validating the predictions on normal control. Resources 6.8).…”
Section: Quantitative Rules Associated With Disease-specificsupporting
confidence: 64%
“…As earlier mentioned, these nanovesicles can express several macromolecules including surface proteins that can facilitate the uptake of viral nucleic acids. In a recent study, it was revealed that exosomes significantly expressed the intracellular membrane protein, Reticulon 3 (RTN3), which modulated their uptake of replication-competent hepatitis C virus RNA and some viral nonstructural proteins [ 47 ]. This highlights the ability of exosomes to successfully incorporate infectious viral nucleic acids, serve as reservoirs for persistent infection or favor viral pathogenesis.…”
Section: Molecular Mechanisms Of Exosomes Biogenesis and Compositionmentioning
confidence: 99%
“…The RHD of RTN3L may be able to mediate ER membrane bending and subsequent serving from the network to form fragments during ER-phagy. It has also been reported that the RHD of RTN3L promotes the formation and efflux of Hepatitis C Virus (HCV) exosomes [ 43 ]. And LIRs of RTN3L also have other functions besides interacting with LC3/GABARAP.…”
Section: Key Molecules Of Er-phagy (Receptors Cofactors Etc)mentioning
confidence: 99%
“…The membrane bending ability of RTNs presumably provides the flexibility of ER membrane to facilitate the viral escape [ 116 , 122 ]. Similarly, RTN3L can induce the bending of the ER membrane and promote the formation and excretion of exosomes that contain HCV [ 43 ]. Under viral infection conditions, RTNs are hijacked by the virus to help their escape and the physiological functions of RTNs in ER-phagy may be impaired.…”
Section: The Diseases Relevance Of Er-phagymentioning
confidence: 99%